1999
DOI: 10.1016/s0022-5223(99)70377-6
|View full text |Cite
|
Sign up to set email alerts
|

Node status in transmural esophageal adenocarcinoma and outcome after en bloc esophagectomy

Abstract: En bloc esophagectomy in patients with transmural esophageal adenocarcinoma is required to obtain the survival benefit of an R0 resection, to adequately assess lymphatic tumor burden, and to be able to predict the likelihood of recurrence and death and thereby guide the use of postoperative adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
82
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 13 publications
4
82
2
Order By: Relevance
“…In addition, the presence and the number of lymph node metastases in these patients was the most significant predictor of survival. 6 Those investigators found that the 5-year survival rate was 23% in patients with Յ 4 involved lymph nodes, but the rate decreased to 12% for patients with Ͼ 4 lymph node metastases. Correspondingly, the likelihood of developing recurrent disease increased from 53% to 90%, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In addition, the presence and the number of lymph node metastases in these patients was the most significant predictor of survival. 6 Those investigators found that the 5-year survival rate was 23% in patients with Յ 4 involved lymph nodes, but the rate decreased to 12% for patients with Ͼ 4 lymph node metastases. Correspondingly, the likelihood of developing recurrent disease increased from 53% to 90%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…We also showed that, the higher the number of lymph nodes involved, as well as the ratio of positive lymph nodes, the poorer the survival of patients with esophageal carcinoma. One study 6 found that the number of involved lymph nodes, irrespective of the depth of tumor invasion, was correlated with the subsequent development of systemic metastasis: 0% for patients with no involved lymph nodes, 45% for patients with 1-4 involved lymph nodes, 80% for patients with 5-9 involved lymph nodes, and 92% for patients with Ͼ 10 involved lymph nodes. In addition, the presence and the number of lymph node metastases in these patients was the most significant predictor of survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations